Determinasi Kemiskinan Perdesaan di Indonesia - Dian Nora Herlina; Kikin Windhani (Jurnal Mahasiswa Manajemen dan Akuntansi, 2025)
The purpose of this study is to analyze the effect of village fund realization, human development index, realization of the number of families receiving food social assistance, and the Gini ratio of rural areas on the percentage of poor people in rural areas in Indonesia. This is a quantitative study, located in Indonesia with case studies from 2018 to 2023. The data analysis technique used panel data regression analysis. The results show that the realization of village funds, the human development index, and the realization of the number of families receiving food social assistance have a significant negative effect on the percentage of poor people in rural areas in Indonesia, while the Gini ratio of rural areas has a significant positive effect on the percentage of poor people in rural areas in Indonesia. The implications of this study indicate that the government needs to optimize the use of village funds for productive activities, improve the quality of education, health, and job skills, and ensure that food social assistance is targeted accurately through accurate data collection. Additionally, policies for equitable village development must be strengthened through income diversification, access to capital for the poor, and community-based economic development.